LARGE WILDLIFE POPULATION IN BAGHMARA BUFFER ZONE COMMUNITY FOREST, NEPAL - Sharma, B. K.; Chalise, M. K.; Solanki, G. S. (Ecoprint: An International Journal of Ecology, 2013)
A year round monitoring of large wild mammals was conducted from April 2010 to March 2011 in Baghmara Buffer Zone Community forest at central lowland area of Nepal. The main objective of the study was to assess large wild mammals’ population in pre– and post– community management period. Direct observations either by establishment of transects passing through different habitats or scan count of the total area were applied to find out the population of large mammals. During precommunity management period, only two large wild mammals were reported, and one was resident and other was frequent visitor from nearby National Park. In the post-community management period, the number of resident large mammals increased to nine species. Now the area has become a safe breeding habitat for those large mammals. DOI: http://dx.doi.org/10.3126/eco.v18i0.9411 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 55-62 Uploaded date: 12/22/2013